DESAIN DAN UJI COBA APLIKASI PEMBELAJARAN KIMIA BERBASIS ANDROID MENGGUNAKAN APPYPIE SEBAGAI MEDIA PEMBELAJARAN PADA MATERI TATA NAMA SENYAWAwa - Wulandari, Ria; Refelita, Fitri; Utami, Lisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
AbstractThis research aimed at developing a product in the form of Android Based Chemistry learning application using Appypie as an instructional media on Compound Nomenclature lesson. This research was administered at State Senior High School 1 Siak Hulu. Designing Android based Chemistry instructional media was done by using development model adapting five early stages of Borg and Gall model. The subjects of this research were learning material experts, media design experts, Chemistry subject teachers, and the students. The object was Android based instructional media using Appypie. Instruments of this research were validity and practicality test questionnaires. Research findings showed that Android based instructional media using Appypie was stated valid with 78% percentage (valid) by material experts and 89% by the experts of Android based instructional media using Appypie. The designed media was stated practical by Chemistry subject teachers and students, 82 % percentage (very practical) was by Chemistry subject teachers and 87 % percentage (very practical) was by students. Based on these results, it could be concluded that Android based Chemistry learning application using Appypie as an instructional media on Compound Nomenclature lesson was valid and practical to be an instructional media at a school. Keywords: Instructional Media, Android, Appypie, Compound Nomenclature AbstrakPenelitian ini bertujuan untuk menghasilkan produk berupa aplikasi pembelajaran kimia berbasis android menggunakan “Appypie” sebagai media pembelajaran pada materi tata nama senyawa, penelitian ini dilakukan di SMA Negeri 1 Siak Hulu. Desain media pembelajaran kimia berbasis android dilakukan dengan menggunakan model pengembangan yang mengadaptasi lima tahap awal model Borg dan Gall. Subjek penelitian adalah ahli meteri pembelajaran, ahli desain media, guru kimia dan peserta didik di SMA Negeri 1 Siak Hulu dan objek penelitian adalah media pembelajaran berbasis android menggunakan “Appypie”. Instrumen penelitian yang di gunakan berupa data angket uji validitas dan angket uji praktikalitas. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis android menggunakan “Appypie” dinyatakan valid dengan persentase 78% (valid)